Mediation effect of hope on the relationship between inner strength and self-management in patients after percutaneous coronary intervention - Shang, Shuhua; Zheng, Xuemei; Xu, Zhongmei; Sun, Si; Huang, Tianyi (Frontiers in Psychology, 2024)
Background Effective self-management can enhance a patient’s quality of life and delay disease progression. However, motivating patients to adhere to self-management behavior following percutaneous coronary intervention (PCI) remains a challenge. With the robust development of positive psychology and interdisciplinary research, the role of psychology factors in patients’ health behavior has increasingly garnered attention. This study, focusing on positive psychological qualities, aims to investigate the relationship between inner strength, hope, and self-management in patients post-PCI, and to analyze the mediating role of hope between inner strength and self-management. Methods A cross-sectional survey was conducted among 216 PCI patients from a tertiary hospital in Nanjing. Research instruments included a self-designed general information questionnaire, the Inner Strength Scale (ISS), the Herth Hope Index (HHI), and the Coronary Self-Management Scale (CSMS). T-test, analysis of variance, Pearson’s correlation analysis, and mediating effect test were utilized for statistical analysis. Results The average scores of the ISS, HHI, and CSMS were 81.46 ± 12.00, 35.94 ± 5.38, and 86.79 ± 14.84, respectively. Inner strength was positively correlated with hope and self-management (r = 0.867, r = 0.630, respectively; all P < 0.05), and hope was positively correlated with self-management (r = 0.671, P < 0.05). Moreover, hope had a complete mediating effect between inner strength and self-management (β = 0.630, P < 0.01). Conclusion The inner strength, hope, and self-management of patients with PCI are at a moderate level. Inner strength primarily influences patients’ self-management behavior through hope, suggesting that medical staff can target hope to help patients build confidence in life after illness, form and accumulate inner strength, thereby promoting their self-management and improving prognosis.